RELATIONSHIP CHARACTERISTICS AND COMMUNITY BEHAVIOR WITH THE INCIDENCE OF SCHISTOSOMIASIS IN THE WORK AREA OF WUASA COMMUNITY HEALTH CENTER IN 2022 - Rosamey Elleke Langitan (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Schistosomiasis is a zoonotic disease and a public health problem. The cause is a type of worm parasite from the schistosomatidae family which has a habitat in the blood vessels around the intestines or bladder. Schistosomiasis is a parasitic disease caused by blood trematode worms of the genus Schistosoma. Chronic schistosomiasis can reduce the ability of sufferers to work, and in some cases cause death. This study aims to get an overview of the factors that cause recurrent schistosomiasis or reinfection that occurs in the community. Descriptive correlation with the analytic case control study approach, namely retrospective observational analytic research where effects or outcomes are traced back to identify relationships by comparing cases and controls. Sampling in this study were patients who were infected with schistosomiasis as case respondents and those who were not infected with schistosomiasis as control respondents. There is a relationship between the behavior of the community or respondents who are often active in rivers or ditches, often passing through conch focus areas and not utilizing health service facilities with the incidence of respondent schistosomiasis in the community in North Lore District, Poso Regency, Central Sulawesi Province. Conversely, there is no relationship between the characteristics of the respondents which include age, gender, education level, marital status and employment with the incidence of schistosomiasis. Conclusion, the habitual behavior of respondents who often move in the river is related to the incidence of disease schistosomiasis, so that it can be concluded that the main factor causing someone to suffer from schistosomiasis is not due to the characteristics of the respondents in the community in North Lore sub-district, Poso Regency, Central Sulawesi Province.